EL HARAKAH : Mu'jizatu Al-Quraani Al-Kariimi Khasaa'isuhaa Wa Atsaruhaa 'Alaa Tsaqaafati Asy-Syu'uubi - Bakri Muhammad Bahit Ahmad (UIN Maulana Malik Ibrahim, 2017)
This study explores the miracle of the Quran as well as its superiorities given by Allah that distinguish it from the other miracles.